Young Africans' social representations of rape in their HIV-related creative narratives, 2005–2014: Rape myths and alternative narratives. (February 2018) - Singleton, Robyn; Winskell, Kate; Nkambule-Vilakati, Siphiwe; Sabben, Gaëlle
Abstract: Sexual violence is both a major human rights issue and an important driver of HIV infection in sub-Saharan Africa. While quantitative indicators of sexual violence have evolved to facilitate cross-national comparison and country-level decision making, qualitative findings typically remain constrained to single sites and populations. We analyzed social representations of sexual violence, specifically rape, in a sample of 1446 narratives about HIV written by young Africans between 2005 and 2014. The narratives were written at 5 discrete time points (2005, 2008, 2011, 2013 and 2014) by equal numbers of males and females aged 10–24 in urban and rural areas of Swaziland, Kenya, South-East Nigeria, Burkina Faso and Senegal. We combined three analytical approaches: descriptive statistics of quantifiable characteristics of the narratives, thematic data analysis, and a narrative-based approach. Violent rapes by strangers occur in all country samples, but in Nigerian narratives the 'immoral' behavior of female characters facilitates these attacks. Swazi narratives, in contrast, often depict familial rapes that include disclosure and service seeking as key components of the rape scenario. The social representations found in the narrative data reflect rape myths, which, at the socio-cultural level, serve to trivialize sexual violence by minimizing or justifying aggression, thus shifting blame to victims and absolving perpetrators of blame. Additionally, these social representations conflict with self-report data from Violence Against Children surveys conducted in Swaziland (2007), Kenya (2010) and Nigeria (2014) in that they depict perpetrators primarily as strangers or family members as opposed to romantic partners; however, social representations and self-report concur regarding barriers to disclosure and service seeking for victims. The Swazi narratives offer potential models for the framing of sexual violence in ways that promote disclosure and support for survivors and counteract harmful rape myths. Highlights: Distinctive analysis of rape in young Africans' creative narratives on HIV. Cross-national and longitudinal secondary data analysis using triangulating methods. Reveals differences in prominence of common rape myths across countries, with little change over time. Provides recommendations for use of results to address pro-violence norms.